2009
DOI: 10.1007/s00702-009-0269-y
|View full text |Cite
|
Sign up to set email alerts
|

Functional MRI in the assessment of cortical activation during gait-related imaginary tasks

Abstract: Imaginary tasks can be used to investigate the neurophysiology of gait. In this study, we explored the cortical control of gait-related imagery in 21 healthy volunteers using functional magnetic resonance imaging. Imaginary tasks included gait initiation, stepping over an obstacle, and gait termination. Subjects watched a video clip that showed an actor in gait motion under an event-related design. We detected activation in the supplementary motor area during major gait-related imagery tasks, and especially du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 45 publications
5
36
0
Order By: Relevance
“…The bilateral activation in the motor cortex involved the area devoted to the lower limbs representation of Penfield (1954), confirming that subjects performed the task. These data are in line with prior work demonstrating that imagery of gait is a good tool to study real locomotion (Wang et al, 2009), even if some differences exist (Fink et al, 1997;la Fougère et al, 2010). As illustrated on Figure 1 A, the upper activations associated with the imagery of gait task are located, compared with the Penfield's (1954) homunculus, in motor cortical areas corresponding to the pelvic belt and upper muscles of the lower limbs, which are involved in the initiation and the continuing execution of gait.…”
Section: Discussionsupporting
confidence: 89%
“…The bilateral activation in the motor cortex involved the area devoted to the lower limbs representation of Penfield (1954), confirming that subjects performed the task. These data are in line with prior work demonstrating that imagery of gait is a good tool to study real locomotion (Wang et al, 2009), even if some differences exist (Fink et al, 1997;la Fougère et al, 2010). As illustrated on Figure 1 A, the upper activations associated with the imagery of gait task are located, compared with the Penfield's (1954) homunculus, in motor cortical areas corresponding to the pelvic belt and upper muscles of the lower limbs, which are involved in the initiation and the continuing execution of gait.…”
Section: Discussionsupporting
confidence: 89%
“…Brain areas that show higher activation when crossing obstacles are SMA (Malouin et al, 2003;Wai et al, 2012;Wang et al, 2009), visual regions (Malouin et al, 2003;Wang et al, 2009), parietal lobule (Malouin et al, 2003;Wai et al, 2012;Wang et al, 2009) and M1 (Wai et al, 2012;Wang et al, 2009). Additionally, parahippocampal gyrus (Malouin et al, 2003), cingulate cortex, insula and putamen ) showed higher activations.…”
Section: Brain Activity Of Healthy People During Gait Imagerymentioning
confidence: 98%
“…[27][28][29][30] Both the frontal and parietal lobes have been implicated in the control of gait. 31,32 In contrast, executive function has long been associated with activity in the prefrontal cortex in healthy adults and in people with PD. 33,34 Cognitive tests specific to prefrontal function have been significantly associated with postural stability in patients with early to moderate PD.…”
Section: Cognitive and Gait Performance In Parkinson Diseasementioning
confidence: 99%